2002
DOI: 10.4049/jimmunol.168.9.4262
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Expression of Functional CD137 Receptor by Dendritic Cells

Abstract: Interaction between dendritic cells (DCs) and T cells is a prerequisite for the initiation of a T cell response. The molecular nature of this interaction remains to be fully characterized. We report in this work that freshly isolated mouse splenic DCs and bone marrow-derived DCs express CD137 on the cell surface and in soluble form. Triggering CD137 increased the secretion of IL-6 and IL-12 from DCs. More importantly, infusion of an agonistic mAb to CD137 into naive mice enhanced the ability of DCs to stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
178
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 44 publications
8
178
1
Order By: Relevance
“…Although 4-1BB is mainly involved in regulating activated T lymphocyte functions, expression of 4-1BB has been noted on non-T cells such as B cells, monocytes, macrophages, dendritic cells, eosinophils, and neutrophils (Futagawa et al, 2002;Heinisch et al, 2000;Schwarz et al, 1995;Watts et al, 2005;Wilcox et al, 2002;Yoon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although 4-1BB is mainly involved in regulating activated T lymphocyte functions, expression of 4-1BB has been noted on non-T cells such as B cells, monocytes, macrophages, dendritic cells, eosinophils, and neutrophils (Futagawa et al, 2002;Heinisch et al, 2000;Schwarz et al, 1995;Watts et al, 2005;Wilcox et al, 2002;Yoon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the intracellular signaling pathways downstream of 4-1BB and RANK are very similar [13,14]. Recent studies showed that 4-1BB is expressed on dendritic cells and monocytes as well as on T cells, and modulates the function of these cells [15,16]. Furthermore, reverse signaling through 4-1BBL on monocytes induces the secretion of inflammatory cytokines, monocyte proliferation, and endomitosis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 4-1BB is an inducible protein expressed on the surface of activated T lymphocytes, 3 natural killer (NK) cells, 4 and dendritic cells (DCs). [5][6][7] It is a member of the tumor necrosis factor/nerve growth factor family of receptors that includes CD40, CD27, CD30, and OX-40. Its natural ligand, 4-1BB ligand (4-1BBL), is expressed on activated APC, including B cells, macrophages, and DCs.…”
Section: Introductionmentioning
confidence: 99%
“…9 In vivo activation of 4-1BB signaling by the administration of agonistic 4-1BB antibodies or 4-1BB L-transduced tumor cells resulted in the regression of some tumors. 6,[9][10][11] We previously showed that the combination of 4-1BB costimulation by an agonistic antibody with IL-12 gene transfer induced a significant synergistic antitumor response in a mouse colon carcinoma model. In order to minimize the inherent dangers involved with the introduction of foreign antigen, for example, agonistic antibody, to patients in future clinical trials, we further tested the efficacy of an adenovirus (ADV) expressing membrane-bound 4-1BBL (ADV/4-1BBLm), which is the natural ligand for this receptor.…”
Section: Introductionmentioning
confidence: 99%